A comparison between the knowledge and attitude of private and public universities dental student regarding HIV, Riyadh, Saudi Arabia - Alotaibi, Sultan; Al hamwi, Saleem; Albahli, Hamad; Alharbi, Fahad; Aldahyan, Abdulaziz; Shenoy, Mahesh (International Journal of Health Sciences, 2023)
Purpose: This study was conduct with an objective to compare between the knowledge and attitude of private and public universities' dental students regarding HIV, Riyadh, Saudi Arabia. Methodology: An online questionnaire was used to collect the data from dental students of public and private universities. Questionnaire was pre-coded and included closed ended questions. Data was analyzed by IBS SPSS version 21. Descriptive statistics such as frequencies and percentages were computed to describe the demographic information about dental students such as academic level, gender, university and age. Results: most of the students (90.0 %) were aware that "HIV/AIDS can be transmitted to dental workers" and majority of the students (85.5 %) knew that "HIV/AIDS can be diagnosed with oral manifestations". Similarly most of the students (87.1 %) knew that "HIV can be transmitted through Needle injury" and (84.7 %) students aware that "The dentist must provide dental treatment for HIV-positive". It was noted that (81.7 %) and (85.3 %) of the students knew that "Hepatitis more transmissible than HIV/AIDS" and "Medical staff is more susceptible to HIV transmission", respectively. More than half of the students (66.7 %) and (76.1 %) responded that "You will perform CPR if HIV/AIDS patients need it" and "Patients with HIV/AIDS can live in the same place with others", respectively. In general, knowledge and attitude towards HIV/AIDS of dental student was examined. It was concluded that students have good knowledge about HIV/AIDS but there attitudes towards HIV/AIDS was not good. Therefore, more efforts are required to improve the attitudes of future dentists. Unique Contribution to Theory, Policy and Practice: The results of this study show the importance and necessity of medical courses that deal with the subject of HIV/AIDS, focusing not just on furthering HIV knowledge but also on dealing with stigma, anxiety and misperceptions about HIV/AIDS and PLWHA. In addition, it is extremely important to conduct these courses before the students start their clinical studies so that correct and sufficient knowledge and attitudes, which are required when dealing with patients, are already well embedded in the students' minds by that time.